The impact of green tea polyphenols on development and reproduction in Drosophila melanogaster. (January 2016) - Lopez, Terry E.; Pham, Hoang M.; Barbour, Julia; Tran, Phillip; Van Nguyen, Benjamin; Hogan, Sean P.; Homo, Richelle L.; Coskun, Volkan; Schriner, Samuel E.; Jafari, Mahtab
Highlights: Fruit fly larvae were exposed to green tea polyphenols (GTP) only during development. A high dose delayed development reduced offspring sizes and impaired reproduction. Morphological abnormalities of reproductive organs were observed. High doses of GTP may cause developmental adverse effects in humans. Abstract: Although green tea has numerous health benefits, adverse effects with excessive consumption have been reported. Using Drosophila melanogaster, a decrease in male fertility with green tea was evidenced. Here, the extent of green tea toxicity on development and reproduction was investigated. Drosophila melanogaster embryos and larvae were exposed to various doses of green tea polyphenols (GTP). Larvae exposed to 10 mg/mL GTP were slower to develop, emerged smaller, and exhibited a dramatic decline in the number of emerged offspring. GTP protected flies against desiccation but sensitised them to starvation and heat stress. Female offspring exhibited a decline in reproductive output and decreased survival while males were unaffected. GTP had a negative impact on reproductive organs in both males and females (e.g., atrophic testes in males, absence of mature eggs in females). Collectively, the data show that high doses of GTP adversely affect development and reproduction of Drosophila melanogaster .